THE ROLE OF PEDAGOGICAL CONDITIONS IN THE TRAINING OF PHYSICAL THERAPISTS - Корчинський, Володимир; Пономаренко, Микола (SWorldJournal, 2025)
The article considers modern aspects of professional training of future physical therapy specialists in higher educational institutions, which involves improving the clinical training of future specialists in this field, the main principles of which are s